Chlamydia Vaccination: Parent Opinions and Implications for Future Promotion Programs. Issue 11 (11th November 2022) - Footman, Alison; Kanney, Nita; Niccolai, Linda M.; Zimet, Gregory D.; Overton, Edgar Turner; Davies, Susan L.; Van Der Pol, Barbara
Abstract : A qualitative study on parents' opinions about a potential adolescent chlamydia vaccine found that parents think a vaccine could be beneficial. However, healthcare provider recommendations will be instrumental in promoting uptake. Abstract : Background: Chlamydia vaccines are currently under development and have the potential to lower the incidence of infection and disease, which are highest among adolescents and young adults. Ideally, a chlamydia vaccine would be administered to adolescents before sexual debut, a time when parents are the primary vaccine decision makers. This study explores parent opinions about an adolescent chlamydia vaccine to understand barriers and facilitators to uptake. Methods: Semistructured interviews were conducted with parents of adolescents. Topics included conversations parents have with their children about chlamydia, opinions on chlamydia vaccine development, and vaccine characteristics, such as efficacy and cost. Interviews were analyzed using a thematic analysis approach. Results: From March to April 2021, 21 interviews were completed. Few parents discuss chlamydia with their children and sex education was seen as limited. Overall, 16 parents indicated that a chlamydia vaccine is needed. However, there were mixed opinions about vaccinating their own children, related to the need to vaccinate at a young age, vaccine efficacy, and confusion about benefits of vaccination. Finally, healthcare provider recommendations were seen as important before deciding to vaccinate a child. Conclusions: Although parents think that chlamydia vaccines are needed, lack of awareness about infections and potential benefits of vaccination could serve as barriers to uptake. Healthcare provider recommendations can help to improve knowledge and vaccine uptake. However, there is a need for multilevel approaches to improve chlamydia awareness and ensure that vaccination initiation and completion rates remain high.